Exploring the Practices of Greek Municipalities with Left-wing Majorities between 2014-2019: The Battle for the Commons and the Limits of Action - Vasileiou, Andreas (Identities: Journal for Politics, Gender and Culture, 2019)
Transcript of the presentation by Andreas Vasileiou, held in Skopje on September 14, 2019, within the framework of School for Politics and Critique 2019: Municipal Organizing and Left-wing Environmental Solutions. Author(s): Andreas Vasileiou Title (English): Exploring the Practices of Greek Municipalities with Left-wing Majorities between 2014-2019: The Battle for the Commons and the Limits of Action Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 18-21 Page Count: 4 Citation (English): Andreas Vasileiou, “Exploring the Practices of Greek Municipalities with Left-wing Majorities between 2014-2019: The Battle for the Commons and the Limits of Action,” Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 18-21.